Vinyl polymer and preparation method thereof
By introducing high-content methyl acrylate groups into vinyl polymers and using the ester-based action force, the problem of uneven distribution of polar groups in polyolefin materials is solved, its thermal and mechanical properties are improved, and its thermal performance and mechanical properties are improved, and the Its compatibility with polar resins has been enhanced and the application value of polyethylene is enhanced.
Patent Information
- Application Number
- CN202310758374.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2024-12-27
AI Technical Summary
When the prior art improves the functionality of polyolefin materials, it is difficult to uniformly introduce polar groups, resulting in insufficient thermal properties, mechanical and mechanical properties and aging resistance, and poor compatibility with polar resins, affecting them. Application value.
By introducing high content of methyl acrylate groups into the vinyl polymer, using the intermolecular forces and hydrogen bonds generated by the ester group, a vinyl polymer rich in polar ester groups was prepared, and coordination polymerization was used The polymerization conditions are controlled to ensure uniform distribution and adjustability of polar groups.
The thermal properties, mechanical and aging resistance of polyethylene are significantly improved, their compatibility with polar resins is improved, the structure of composite polyethylene film materials is simplified, and production costs are reduced.
Smart Images

Figure CN119192447A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a vinyl polymer and a preparation method thereof. Background Art
[0002] Polyolefin is the world's largest and most widely used polymer material. Polyolefin has excellent mechanical strength and processing properties, outstanding chemical corrosion resistance and good electrical insulation properties, and is inexpensive. Polyolefin is widely used in various fields such as transportation, construction, agriculture, national defense construction and people's daily life.
[0003] In order to give polyolefin materials a higher use value, polyolefins will be functionalized. At present, there are four main methods to achieve polyolefin functionalization. 1. High-pressure free radical copolymerization method. Under high temperature and high pressure conditions, ethylene can be copolymerized with a variety of polar monomers, but the free radical copolymer has a complex structure and is uncontrollable. The conditions required for the reaction are very harsh, and the initial equipment investment is relatively large. 2. Post-reaction processing method. Chemical modification of existing polyolefin materials is the so-called post-reaction processing method. At present, most of the commercial functional polyolefins are prepared based on this method. This method has low cost and is easy to operate, but this method requires a high-temperature radiation source, and polymer degradation and cross-linking side reactions often occur, which seriously damages the original excellent properties of the polymer. 3. Reaction intermediate method. Design a functional monomer, introduce the functional group into the polyolefin through copolymerization, thereby obtaining a reactive intermediate, and then convert the functional group into a polar group to obtain a functionalized polyolefin. The key point of this method is to design the reaction functional intermediates, which not only requires the functional monomers to be able to copolymerize with olefin monomers more easily, but also requires the functional groups to be able to be converted into various polar groups. 4. Direct copolymerization method: olefins and polar monomers gently functionalize polyolefins under the action of coordination polymerization catalysts. This method is undoubtedly the most direct method for synthesizing structure-controllable side-functionalized polyolefins. It can not only ensure that the introduced polar groups are randomly distributed on the side groups of polyolefins, but also adjust the number of introduced polar groups by controlling the insertion rate of polar comonomers. Summary of the invention
[0004] In order to make the content of polar methyl acrylate in the polymer moderate and adjustable, the present invention provides a new vinyl polymer product with a high insertion rate of polar ester groups and flexible controllable properties, so as to be suitable for more application scenarios.
[0005] As another aspect of the present invention, it relates to a vinyl polymer, wherein the vinyl polymer is as shown in formula (I):
[0006]
[0007] In formula (I), m, n, and x are all integers ≥ 1;
[0008] In the molecular chain of formula (I):
[0009] With A chain segment groups introduced by the methyl acrylate, as shown in formula (II):
[0010] With a B segment group introduced by the ethylene, as shown in formula (III): It also has a C chain segment group introduced by the ethylene, as shown in formula (IV):
[0011] The A segment group is located at the end of the vinyl polymer main chain and / or the vinyl polymer side chain; the C segment group is located at the vinyl main chain;
[0012] Based on the total molar amount of the A chain segment group and the B chain segment group, the molar amount of the A chain segment group is 60 to 90 mol%; the molar amount of the B chain segment group is 10 to 40 mol%;
[0013] Based on the total molar amount of the A chain segment group, the B chain segment group and the C chain segment group, the sum of the molar amounts of the A chain segment group and the B chain segment group is 5 to 20 mol%; the molar amount of the C chain segment group is 80 to 95 mol%;
[0014] In a specific embodiment, based on the total molar amount of the A chain segment groups and the B chain segment groups, the molar amount of the A chain segment groups is 70-90 mol%; the molar amount of the B chain segment groups is 10-30 mol%.
[0015] In a specific embodiment, based on the total molar amount of the A chain segment group, the B chain segment group and the C chain segment group (calculated as 100 mol%), the sum of the molar amounts of the A chain segment group and the B chain segment group is 10 to 20 mol%; the molar amount of the C chain segment group is 80 to 90 mol%.
[0016] In a specific embodiment, the branching degree of the vinyl polymer is 5 to 50 branches / 1000C.
[0017] Furthermore, the branching degree of the vinyl polymer is 5 to 20 branches / 1000C.
[0018] In a specific embodiment, the weight average molecular weight of the vinyl polymer is not less than 1×10 4 g / mol and less than 1×10 6 g / mol, molecular weight distribution 1~3.
[0019] Furthermore, the weight average molecular weight of the vinyl polymer is not less than 1×10 5 g / mol, molecular weight distribution 1~2.
[0020] In a specific embodiment, the density of the vinyl polymer is 0.940 to 0.970 Kg / m 3 , melt flow index 1 ~ 10g / 10min, melting point 105 ~ 130 ℃, water contact angle does not exceed 90°.
[0021] Furthermore, the density of the vinyl polymer is 0.940 to 0.960 Kg / m 3 , the melt flow index is 1-5g / 10min, the melting point is 120-130℃, and the water contact angle does not exceed 85°.
[0022] As another aspect of the present invention, it relates to a method for preparing the above-mentioned vinyl polymer, comprising the following preparation steps:
[0023] A1. In an ethylene atmosphere, add catalyst, methyl acrylate and ethylene in sequence, control the polymerization temperature to be 20-100°C, the polymerization pressure to be 0.5-10 MPa, and the polymerization time to be 0.5-4 h;
[0024] A2, releasing the pressure after reaching the polymerization time, adding acidic ethanol to the reaction solution to terminate the polymerization and obtain a polymer;
[0025] A3. Filter and wash the polymer obtained in A2, and then vacuum dry it to constant weight to obtain a vinyl polymer.
[0026] In a specific embodiment, in A1, the catalyst is as shown in formula (V):
[0027] In formula (I), R1 is selected from phenyl or 2,4,6-trinitrilephenyl; R2 and R3 are independently selected from phenyl or 2,6-dimethoxyphenylphenyl; and R4 is H.
[0028] The present invention introduces polar ester groups (A chain segment groups) into the molecular chains of the vinyl polymers and utilizes the intermolecular forces and hydrogen bonding generated by the ester groups to impart polarity to the vinyl polymers, thereby making the ester groups in the vinyl polymers more evenly distributed, further solving the shortcomings of linear medium and high density vinyl polymers, such as poor compatibility with engineering resins, poor adhesion with non-resin materials such as metals and paper, and poor printability, dyeability, and wettability.
[0029] The vinyl polymer provided by the present invention can be used to fill or reinforce polyethylene, greatly improving the thermal properties and mechanical properties of polyethylene; improving its water absorption, aging resistance and environmental stress cracking resistance, improving the compatibility of general polyethylene and polar resins; simplifying the structure of composite polyethylene film materials and reducing production costs.
[0030] Compared with the post-functionalization technology (blending, grafting), the preparation method adopted by the present invention is that the polar ethylene polymer of the present invention is prepared by coordination polymerization of ethylene and methyl acrylate, and the ester content in the vinyl polymer is higher.
[0031] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is the structural formula of the vinyl polymer of the present invention;
[0033] Figure 2 is the hydrogen spectrum of the vinyl polymer prepared in Example 1 of the present invention;
[0034] Figure 3 This is a temperature curve diagram of the vinyl polymer prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] The medium and high density polyethylene currently on the market has a crystallinity of 80% to 90%, a softening point of 125 to 135°C, an operating temperature of 100°C, and good properties such as hardness and tensile strength. However, due to the lack of polar groups in its structure, the product has low water absorption, poor aging resistance, poor resistance to environmental stress cracking, a low heat deformation temperature under stress, and poor compatibility with polar resins.
[0036] In order to improve the above phenomenon, the inventors have found through a large number of literature studies that there were attempts to introduce polar groups into medium and high density polyethylene by post-functionalization in the early stage. For example, Chengdu University of Science and Technology introduced maleic anhydride groups into high density polyethylene by electron beam irradiation grafting (Chemical Research and Application, 1994, (6), 4, 92-94); Changchun Institute of Applied Chemistry of the Chinese Academy of Sciences introduced ethyl acrylate into high density polyethylene (Polymer Materials Science and Engineering, 1995, (11), 5, 11-15); Beijing University of Chemical Technology investigated the effect of introducing polar monomers such as acrylic acid and 2-hydroxyethyl methacrylate into powdered high density polyethylene by a similar method (Chemical Journal, 2002, (53), 6, 640-643). The above literatures all introduced polar groups into polyethylene chains by grafting. However, the grafting rate could only reach about 3%. The homopolymer of polar monomers also existed in the product, and different degrees of cross-linking would occur. In addition, the prior art also uses high-pressure free radical polymerization technology to produce polar vinyl polymer products, but this method is difficult to obtain linear medium- and high-density polar vinyl polymers.
[0037] When the inventor reviewed the methods for preparing polar vinyl polymer products in recent years, he found that: currently, there are mainly three types of late transition metal catalysts that can obtain linear polar copolymers by coordination polymerization: CN106589180B, CN109320558B, CN113651909A, etc. disclose phosphine-phenol type late transition metal catalysts for copolymerization of ethylene and polar monomers, CN109021013B, CN108864329B, etc. disclose phosphine-sulfonic acid late transition metal catalysts for copolymerization of ethylene and polar monomers, CN105061505A, CN108017670B, etc. disclose bisphosphine type late transition metal catalysts for copolymerization of ethylene and polar monomers, but these studies still focus on the innovation of catalyst structure, and there is little research on polar vinyl polymers obtained by coordination polymerization using late transition metal catalysts.
[0038] In summary, given that the prior art is not as good as the inventors' expectations, the inventors made the present invention through further research and development.
[0039] The present invention further improves the content (insertion rate) of polar methyl acrylate inserted into the polymer on the basis of post-functionalization and can flexibly control it; the content of methyl acrylate in the polymer can be moderate and adjustable, and the molecular weight of the polymer can reach more than 10,000 (even more than 100,000 in the best case), and the polymer product prepared by the present invention has high application value.
[0040] The present invention is further described below in conjunction with specific embodiments, and the protection scope of the present invention is not limited by the following embodiments. The sources of the materials mainly involved in the embodiments are shown in Table 1 below, and other materials not shown are conventional commercial products.
[0041] Table 1 Material source description
[0042]
[0043]
[0044] Among them, the equipment used in the embodiments of the present invention, such as the 250ml pressure-resistant reactor and the 10L pressure-resistant reactor, are both manufactured by Yantai Keli Chemical Equipment Co., Ltd.
[0045] The following are Examples 1 to 9 of the present invention. The catalysts used in Examples 1 to 9 are all prepared by the following method. Specifically, the following steps are included:
[0046] S1. Under nitrogen protection, 2-phenylphenol (50 mmol) was dissolved in 100 mL of anhydrous ethanol. At 0°C, 22 mL of n-butyl lithium was added, and the dripping rate was controlled to be 10-15 drops / min. Then, the mixture was reacted at room temperature for 5 h to obtain a large amount of white precipitate A.
[0047] S2, dissolve 14.6 g of 2-bromo-2,6-dimethoxybiphenyl in 100 mL of tetrahydrofuran, cool to room temperature, add 49.8 mmol of n-butyl lithium solution, react for 3 h to obtain a white turbid solution, add 50 mmol of phenylphosphine dichloride in tetrahydrofuran solution, react at room temperature for 5 h to obtain a solution B of CIPPh (2-2,6-dimethoxybiphenyl), and cool to room temperature;
[0048] S3, add the white precipitate A to the solution B of CIPPh (2-2,6-dimethoxybiphenyl) at a rate of 10-15 drops / min, react at room temperature for more than 12 hours, add 200 ml of deionized water after the reaction, extract the organic phase with 2 volumes of ether, concentrate the obtained organic phase to 100 ml, deoxygenate by freezing cycle, add 5 ml of concentrated hydrochloric acid under nitrogen protection, react for 5 hours, track the reaction by thin layer chromatography (TLC) until it is fully completed, adjust the pH to 7 with sodium bicarbonate aqueous solution, add 100 ml of deionized water, extract the organic phase with 2 volumes of ether, dry with 25 g of anhydrous sodium sulfate, concentrate, and obtain white ligand C14 g by column chromatography with a yield of about 70%;
[0049] S4. Under nitrogen protection, ligand C (0.8 mmol) was dissolved in 50 mL of dry toluene, and added dropwise to a toluene solution containing 1 mmol of Py2Ni(CH2)2 at a rate of 10-15 drops / min. The reaction was stirred at room temperature for 5 h, filtered, and washed three times with 50 mL of toluene. The filtrate and washing liquid were combined, concentrated under reduced pressure to 2 mL, and 10 mL of n-hexane was added for recrystallization. The dripping rate was controlled to be 10-15 drops / min to obtain 0.36 g of brown-yellow crystals with a yield of about 80%.
[0050] The structure of the brown-yellow crystalline catalyst (a) obtained by the above preparation method is:
[0051] In the formula: Ph is phenyl, Ar = 2,6-dimethoxyphenylphenyl.
[0052] The following are Examples 1 to 9 of the present invention. The following examples use a phosphine-phenol type late transition metal catalyst represented by formula (a) to catalyze the copolymerization of ethylene and methyl acrylate to prepare polar medium-high density (0.940-0.970 Kg / m 3 ) Vinyl polymer.
[0053] Example 1
[0054] The polymerization reaction of this embodiment is completed in a 250mL stainless steel pressure-resistant reactor with mechanical stirring, and the reactor cover is provided with a pressure-resistant liquid feeding pipe. The vinyl polymer prepared in this embodiment is prepared by the following steps:
[0055] A1. Replace the reactor with 0.1MPa nitrogen three times to exhaust the air in the reactor. Heat the reactor to 150°C under -0.1MPa vacuum, keep the temperature constant for 2h, and then cool to room temperature. Replace the reactor with 0.1MPa nitrogen three times again, and then pressurize the reactor with 0.1MPa ethylene to 0.1MPa, and replace three times;
[0056] A2, under ethylene atmosphere, at room temperature, add 30 μmol of the catalyst in toluene solution into the reactor through a feeding tube, and then add about 3 ml of methyl acrylate (the amount added is controlled to be 1-5 ml), and the total reaction volume is maintained at 150 mL;
[0057] A3. Raise the temperature of the reactor to 30°C through an electric heater (the reaction temperature is controlled by the deionized water introduced into the reactor coil and the electric heater, and is monitored by an internal thermocouple with a temperature control accuracy of ±1°C). After reaching the reaction temperature, add ethylene and maintain the reactor pressure at 0.5MPa. After reacting for 4 hours, release the ethylene pressure and add 0.5 times the volume of the reaction solution of 5% (v / v) acidic ethanol to terminate the polymerization;
[0058] A4. Collect the obtained polymer, filter it, wash it with ethanol 2-3 times, and then dry it under vacuum at 60°C to constant weight.
[0059] The hydrogen spectrum of the vinyl polymer prepared in this example is shown in the attached Figure 2 , see the attached diagram for the cooling and heating curves Figure 3 .
[0060] Large-scale polymerization reactions can be completed in a 10L high-pressure reactor with a pressure-resistant liquid feeding pipe on the reactor cover. The amount of ethylene and nitrogen can be measured by an online mass flow meter. The reaction temperature is evenly raised by electrically heating the heat transfer oil in the outer jacket of the reactor. The outer jacket of the reactor is equipped with a coil, through which deionized water or other cooling media can be passed for cooling. The reaction temperature is controlled to be constant between 30 and 100°C by adjusting the flow of cooling water online and heating the heat transfer oil through an electric heater. The temperature is monitored by a thermocouple inside the reactor and the signal required by the temperature controller is fed back. The temperature control accuracy is
[0061] ±1℃. Similarly, replace the reactor with 0.1MPa nitrogen three times to exhaust the air in the reactor. Heat the reactor to 150℃ under -0.1MPa vacuum, keep constant temperature for 2h, and then cool to room temperature. Replace the reactor with 0.1MPa nitrogen three times again, and then pressurize the reactor with 0.1MPa ethylene to 0.1MPa, and replace three times. At room temperature, under ethylene atmosphere, add 30mmol of catalyst toluene solution to the reactor through the feeding tube, and then add 1-100ml of methyl acrylate, and the total reaction volume is maintained at 6L. Raise the temperature of the reactor to the reaction temperature through an electric heater. After the temperature reaches 30-100℃, fill in ethylene and keep the pressure of the reactor at 0.5-10MPa. After reacting for 1-8h, release the ethylene pressure and add 1L of acidic methanol to terminate the polymerization. Introduce the reactants into the separator from the discharge valve at the bottom of the reactor. The separator is a two-layer structure with a stirring device suitable for solid-liquid systems on the upper part, and a filter screen is installed between the upper and lower layers. Start the stirring of the separator, and the liquid in the reactant will automatically fall into the lower part of the separator, and then be introduced into another closed container for recycling. Hot dry nitrogen or air flow is introduced into the lower part of the separator to dry the solid reactants remaining on the upper part of the separator screen, and the gas is discharged at the top of the separator. The organic content in the gas is regularly tested. When the organic content is ≤100ppm, the solid reactants in the separator are collected, washed with ethanol, filtered, and dried several times, and finally dried to constant weight under vacuum at 60°C.
[0062] The difference between Examples 2 to 9 and Example 1 is that the polymerization reaction conditions are different. See Table 2 below for details.
[0063] Table 2 Description of polymerization process parameters of Examples 1 to 9
[0064]
[0065]
[0066] Performance Testing
[0067] The polar vinyl polymers prepared in Examples 1 to 9 above were subjected to the following performance tests, and the test results are recorded in Table 3 below.
[0068] 1. Structural analysis of polymers
[0069] The Bruker-500 nuclear magnetic resonance instrument from Swiss Bruker was used.
[0070] 1 H NMR test conditions: frequency 300 Hz, 120 °C, CDCl3 as solvent.
[0071] 13 C NMR test conditions: frequency 75 Hz, CDCl3 as solvent, tilt angle 74°, delay time 4 s, sampling time 1.5 s, determination method: proton decoupling method.
[0072] 2. Polymer weight average molecular weight (Mw) and molecular weight distribution
[0073] The CR-7 gel permeation chromatograph of PE Company of the United States was used. The conditions were: 135°C, 1,2,4-trichlorobenzene as eluent, and flow rate of 1.0 mL / min.
[0074] 3. Melting point of polymer
[0075] A differential scanning calorimeter Q2000 from TE Corporation of the United States was used. The temperature was raised to 170°C at a rate of 10°C / min, maintained for 5 min, and then lowered to 50°C at a rate of 10°C / min, and the temperature drop and temperature rise curves were recorded.
[0076] 4. Density of polymer
[0077] The analysis was carried out according to the method in GB / T10332-2010, using a 6001 density meter from CEAST, Italy.
[0078] 5. Melt flow index (MI) of polymer
[0079] According to the method in GB / T 3682-2018, the melt flow rate meter of CEAST, Italy, was used, with a die diameter of 2.095 cm, a temperature of 190°C, an accuracy of 0.1°C, and a load of 2.16 kg.
[0080] 6. Water contact angle of polymer
[0081] The test was conducted using a G-1 contact angle measuring instrument produced by Kyowa, Japan. Deionized water was dropped on the film surface for 1 min before testing. Three points 5 mm apart were measured for each sample, and a total of 6 readings were taken, with the arithmetic average taken. The drop volume was controlled at 1-5 μl.
[0082] 7. Calculation of ester content in polymer
[0083] The calculation is performed according to the method provided in Patent No. CN107001542B.
[0084] Table 3 Performance test data of Examples 1 to 9
[0085]
[0086]
[0087] Note: 1. The molar ratio of A based on the total number of moles of all chain segments being 100. 2. The molar ratio based on A+B=100. 3. The molar ratio based on A+B+C=100.
[0088] Based on the above performance test data, the inventors believe that: the catalyst (a) used in the above embodiment has a phenyl group and a 2,6-dimethoxyphenylphenyl group at the P atom end to maintain sufficient steric hindrance around the P atom, and at the same time, a large steric hindrance phenyl group is also present at the ortho position of O, further increasing the steric hindrance. The large steric hindrance substituent blocks the dsp 2 The hybrid Ni center pz empty orbital prevents the copolymer monomer from approaching the metal center axially. At the same time, the crowded space also reduces the deactivation of the bimolecular structure, thereby effectively inhibiting the β-H elimination and chain transfer after 2,1 insertion, thereby obtaining a high molecular weight ethylene-methyl acrylate copolymer.
[0089] The following are Examples 10 to 18 of the present invention. The catalysts used in Examples 10 to 18 are all prepared by the following method. Specifically, the following steps are included:
[0090] S1', under nitrogen protection, 2,4,6-trinitrilephenylphenol (50mmol) was dissolved in 100mL of anhydrous ethanol, and 22mL of n-butyl lithium was added at 0°C, the dripping rate was controlled to be 10-15 drops / min, and the reaction was carried out at room temperature for 5h to obtain a large amount of white precipitate A;
[0091] S2, dissolve 14.6 g of 2-bromo-2,6-dimethoxybiphenyl in 100 mL of tetrahydrofuran, cool to room temperature, add 49.8 mmol of n-butyl lithium solution, react for 3 h to obtain a white turbid solution, add 50 mmol of phenylphosphine dichloride in tetrahydrofuran solution, react at room temperature for 5 h to obtain a solution B of CIPPh (2-2,6-dimethoxybiphenyl), and cool to room temperature;
[0092] S3, add the white precipitate A to the solution B of CIPPh (2-2,6-dimethoxybiphenyl) at a rate of 10-15 drops / min, react at room temperature for more than 12 hours, add 200 ml of deionized water after the reaction, extract the organic phase with 2 volumes of ether, concentrate the obtained organic phase to 100 ml, deoxygenate by freezing cycle, add 5 ml of concentrated hydrochloric acid under nitrogen protection, react for 5 hours, track the reaction by thin layer chromatography (TLC) until it is fully completed, adjust the pH to 7 with sodium bicarbonate aqueous solution, add 100 ml of deionized water, extract the organic phase with 2 volumes of ether, dry with 25 g of anhydrous sodium sulfate, concentrate, and obtain white ligand C14 g by column chromatography with a yield of about 70%;
[0093] S4. Under nitrogen protection, ligand C (0.8 mmol) was dissolved in 50 mL of dry toluene, and added dropwise to a toluene solution containing 1 mmol of Py2Ni(CH2)2 at a rate of 10-15 drops / min. The reaction was stirred at room temperature for 5 h, filtered, and washed three times with 50 mL of toluene. The filtrate and washing liquid were combined, concentrated under reduced pressure to 2 mL, and 10 mL of n-hexane was added for recrystallization. The dripping rate was controlled to be 10-15 drops / min to obtain 0.36 g of brown-yellow crystals with a yield of about 80%.
[0094] The structure of the brown-yellow crystalline catalyst (b) obtained by the above preparation method is:
[0095] In the formula: Ph is phenyl, Ar = 2,6-dimethoxyphenylphenyl.
[0096] The difference between the preparation of vinyl polymers in Examples 10 to 18 and Example 1 is that the polymerization process conditions are different. See Table 4 below for details.
[0097] Table 4 Description of polymerization process parameters of Examples 10 to 18
[0098]
[0099] The polar vinyl polymers prepared in Examples 10 to 18 above were subjected to the following performance tests, and the test results are recorded in Table 5 below.
[0100] Table 5 Performance test data of Examples 10 to 18
[0101]
[0102]
[0103] Note: 1. The molar ratio of A based on the total number of moles of all chain segments being 100. 2. The molar ratio based on A+B=100. 3. The molar ratio based on A+B+C=100.
[0104] Based on the above performance test data, the inventors believe that: the catalyst (b) used in the above embodiment, based on the ortho-position of O with a large sterically hindered phenyl group, further introduces F atoms to slow down the direct effect of the ester group on the metal center, and the tendency of the comonomer to approach the metal center in an -O- manner is further weakened. At the same time, the crowded space also reduces the deactivation of the bimolecular molecules, thereby effectively inhibiting the β-H elimination and chain transfer after the 2,1 insertion, and obtaining a high molecular weight ethylene-methyl acrylate copolymer.
[0105] Hereinafter, the inventors selected the existing phosphine-phenol type nickel catalyst in the prior art to catalyze the polymerization reaction between ethylene and methyl acrylate (for the specific polymerization reaction steps of Comparative Examples 1 to 2, see Example 1), and prepared Comparative Examples 1 to 4.
[0106] Comparative Example 1
[0107] The catalyst used in this comparative example is: Among them, the ortho position of O carries t-Bu (tert-butyl), and the ones connected to P are Ph (phenyl) and Ar (2,6-dimethoxyphenylphenyl), respectively;
[0108] Polymerization conditions: 1 MPa, 50°C, 1 h.
[0109] Comparative Example 2
[0110] The catalyst used in this comparative example is: Among them, the ortho position of O bears a pentafluorophenyl group, and the groups connected to P are Ph (phenyl) and Ar (2,6-dimethoxyphenylphenyl), respectively;
[0111] Polymerization conditions: 1 MPa, 50°C, 1 h.
[0112] Comparative Example 3
[0113] The catalyst used in this comparative example is: Among them, there is iPr (isopropyl) at the ortho position of the amino group N, and the NN skeleton group is a dimethyl group.
[0114] The synthesis of the catalyst refers to Macromolecules 2020, 53, 9294-9305, the polymerization of ethylene and methyl acrylate and the analysis and performance testing of the polymer refer to the method provided in CN106589180B, and the experimental results of the polymerization of ethylene and methyl acrylate refer to entry 8 of Table 2 in Macromolecules 2020, 53, 9294-9305, which are simultaneously recorded in Table 6 below.
[0115] Comparative Example 4
[0116] In this comparative example, linear low-density polyethylene (LLDPE, brand 7042) produced by Daqing Petrochemical was used as the basic raw material, methyl acrylate (MA) was used as the monomer, and MA-g-LLDPE was obtained by radiation grafting;
[0117] Polymerization conditions: 0 MPa, 60°C, 10 h.
[0118] The performance test data results of Comparative Examples 1-2 and 4 are recorded in Table 6 below.
[0119] Table 6 Performance data results of comparative examples 1 to 4
[0120]
[0121] Note: 1. The molar ratio of A based on the total number of moles of all chain segments being 100. 2. The molar ratio based on A+B=100. 3. The molar ratio based on A+B+C=100.
[0122] Combining the performance test data results in Table 3, Table 5, and Table 6, we can see that:
[0123] ① The copolymerization activity of Example 5 is higher than that of Comparative Example 1, while the copolymerization activity of Example 11 is equivalent to that of Comparative Example 2. The proportion of A in the polymer (mol%) is higher than that of the comparative example, indicating that the copolymerization performance of the present invention is better than that of the existing catalysts with similar catalyst structures. This may be because the electron-donating group at the ortho-position of O in the catalyst precursor of the present invention weakens the attack effect of the ester group on the active center metal during copolymerization, thereby reducing the loss of the active center.
[0124] ② Compared with Comparative Example 3 of the diimine nickel catalyst, the present invention can obtain a higher proportion of A in the polymer (mol%), a lower degree of alkyl branching, and a significantly improved molecular weight of the polymer.
[0125] ③ Compared with the post-functionalized comparative example 4, the proportion of A in the polymer is 10 mol%, which is higher than the 2.4 mol% of comparative example 4.
[0126] The polymer materials prepared in Example 18 and Comparative Example 4 were used as examples to prepare polyethylene films. The following performance tests were performed on the prepared film materials:
[0127] 1. Tensile strength and elongation at break
[0128] The national standard GB / T 1040.1-2022, plastic tensile properties test method, is used for determination;
[0129] 2. Light transmittance
[0130] Adopt the national standard GB / T 2410-2008, determination of light transmittance and haze of transparent plastics;
[0131] 3. Water contact angle
[0132] The national standard GB / T 30693-2014 is used to measure the contact angle between plastic film and water.
[0133] The above performance test results are recorded in Table 7 below.
[0134] Table 7 Performance test results of Example 18 and Comparative Example 4 for film preparation
[0135] Polymer Type Tensile strength MPa Elongation at break % Transmittance % Water contact angle° Embodiment 2-9 Coordination copolymerization 19 600 90 71 Comparative Example 4 graft 18 460 50 89
[0136] Through the performance test results of the prepared films in Table 7, we can find that the tensile strength, elongation at break, light transmittance and water contact angle of the films prepared by the polymer of the present invention are better than those prepared by using the grafted polymer as raw material.
[0137] The above are only preferred feasible embodiments of the present invention, and the protection scope of the present invention is not limited thereto. Various modifications or applications made according to the above embodiments are within the protection scope of this technical solution.
[0138] Although the specific embodiments of the present invention have been described in detail, it will be understood by those skilled in the art. According to all the teachings disclosed, various modifications and replacements can be made to those details, and these changes are all within the protection scope of the present invention. The full scope of the present invention is given by the attached claims and any equivalents thereof.
Claims
1. A vinyl polymer, characterized in that The vinyl polymer is shown in formula (I): In formula (I), m, n, and x are all integers ≥ 1; In the molecular chain of formula (I): With A chain group introduced by methyl acrylate, as shown in formula (II): With a B chain group introduced by ethylene, as shown in formula (III): It also has a C chain group introduced by ethylene, as shown in formula (IV): The A segment group is located at the end of the vinyl polymer main chain and / or the vinyl polymer side chain; the C segment group is located at the vinyl main chain; Based on the total molar amount of the A chain segment group and the B chain segment group, the molar amount of the A chain segment group is 60 to 90 mol%; the molar amount of the B chain segment group is 10 to 40 mol%; Based on the total molar amount of the A chain segment group, the B chain segment group and the C chain segment group, the sum of the molar amounts of the A chain segment group and the B chain segment group is 5 to 20 mol%; the molar amount of the C chain segment group is 80 to 95 mol%.
2. The vinyl polymer according to claim 1, characterized in that Based on the total molar amount of the A chain segment groups and the B chain segment groups, the molar amount of the A chain segment groups is 70 to 90 mol%; and the molar amount of the B chain segment groups is 10 to 30 mol%.
3. The vinyl polymer according to claim 1, characterized in that Based on the total molar amount of the A chain segment group, the B chain segment group and the C chain segment group, the sum of the molar amounts of the A chain segment group and the B chain segment group is 10-20 mol%; the molar amount of the C chain segment group is 80-90 mol%.
4. The vinyl polymer according to claim 1, characterized in that The branching degree of the vinyl polymer is 5 to 50 branches / 1000C.
5. The vinyl polymer according to claim 4, characterized in that The branching degree of the vinyl polymer is 5 to 20 branches / 1000C.
6. The vinyl polymer according to claim 1, characterized in that The weight average molecular weight of the vinyl polymer is not less than 1×10 4 g / mol and less than 1×10 6 g / mol, molecular weight distribution 1~3.
7. The vinyl polymer according to claim 6, characterized in that The weight average molecular weight of the vinyl polymer is not less than 1×10 5 g / mol, molecular weight distribution 1~2.
8. The vinyl polymer according to claim 1, characterized in that The density of the vinyl polymer is 0.940-0.970 Kg / m 3 , the melt flow index is 1-10g / 10min, the melting point is 105-130°C, and the water contact angle does not exceed 90°.
9. The vinyl polymer according to claim 8, characterized in that The density of the vinyl polymer is 0.940-0.960 Kg / m 3 , the melt flow index is 1-5g / 10min, the melting point is 120-130℃, and the water contact angle does not exceed 85°.
10. A method for preparing a vinyl polymer, characterized in that: The method comprises the following preparation steps: A1. In an ethylene atmosphere, add catalyst, methyl acrylate and ethylene in sequence, control the polymerization temperature to be 20-100°C, the polymerization pressure to be 0.5-10 MPa, and the polymerization time to be 0.5-4 h; A2, releasing the pressure after reaching the polymerization time, adding acidic ethanol to the reaction solution to terminate the polymerization and obtain a polymer; A3. Filter and wash the polymer obtained in A2, and then vacuum dry it to constant weight to obtain a vinyl polymer.
11. The method for preparing a vinyl polymer according to claim 10, characterized in that: In A1, the catalyst is as shown in formula (V): In formula (I), R1 is selected from phenyl or 2,4,6-trinitrilephenyl; R2 and R3 are independently selected from phenyl or 2,6-dimethoxyphenylphenyl; and R4 is H.
Citation Information
Patent Citations
Large-steric-hindrance neutral nickel catalyst, preparation method and application in preparation of ethylene / polar monomer copolymers
CN106589180A
Naphthol skeleton phenol-phosphine neutral nickel catalyst preparation method and application in preparing ethylene / vinyl polar monomer co-polymer
CN109320558A
Hydroxyl phosphorus-phenol -containing nickel catalyst, preparation method thereof and application of hydroxyl phosphorus-phenol nickel-containing catalyst in catalytic coordination copolymerization
CN113651909A
